(untitled) (Journal of the Bangladesh Agricultural University, 2020)
The environment friendly renewable energy (i.e., solar energy) is expanding day by day to mitigate the demand of electricity in the remote areas. Considering the significance of the solar energy, the present study was conducted to explore the core economics of using solar household system and its impact on rural livelihoods and assessing the welfare aspects of such adoption. The survey was conducted in 240 households from February to April of 2018 in four upazilas, namely Madarganj, Roumari, Fulchori and Charvadrason of Jamalpur, Kurigram, Gaibandha and Faridpur districts, respectively. A combination of descriptive and statistical techniques was applied to analyze the data. The results revealed that the age groups of 30-45 years had the maximum frequency of 52.08%. About 70.42% of the household heads were below S.S.C level and 14.16% were S.S.C passed. Among the household heads, about 60.83% were farmers and 8.33% were in other agriculture related occupation. The cash inflow of existing solar panel was Tk. 3520.00 and average salvage value was Tk. 4119.58. Assuming 12% discount rate, NPV was Tk. 18064.17 and BCR was 2.01 as well as IRR 32.39% which was greater than opportunity cost of invested capital. Average 2.07 working hour per day extended after installation of solar home system. Overall socio-economic benefit was increased. About 48.23% households’ quality of life switched to good condition, 32.50% household’s agricultural production increased and 45% households’ social security is in good condition. The adoption of solar panel was economically viable and overall welfare increased in the study areas. J Bangladesh Agril Univ 18(2): 486–491, 2020 https://doi.org/10.5455/JBAU.93384